Kontribusi pajak daerah terhadap Pendapatan Asli Daerah Kabupaten Lembata - Panggabean, Lenny (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
In the Regional Expenditure Revenue Budget (APBD), it is stated that regional tax is one of the sources of revenue that plays an important role, in addition to other sources of regional revenue such as levies, the results of the management of separated regional wealth, and other legitimate local revenue. This study aims to determine how much the regional tax contributed to the original revenue of the district of Lembata for the years 2016–2020. The object of research is the 9 types of regional taxes managed by Bapenda, which is secondary data with quantitative and descriptive research methods. The formulation of the problem in this study is to see how much contribution is given by the 9 types of regional taxes managed by Bapenda to the original revenue of the district of Lembata for four years. The conclusion is that the type of local tax that contributes the most is non-metallic minerals and rocks tax, while the type of tax that contributes the least to the district is entertainment tax. For the regional tax contribution managed by Bapenda, there is only an average of 1% of the original regional income contained in the ABPD of Lembata district.